Respuesta:
[tex]9x^2 - 6x + 1 = 0\\\\\frac{(9x - 3)(9x - 3)}{9}\\\\\frac{3(3x - 1)3(3x - 1)}{9}\\\\(3x - 1)(3x - 1)\\\\3x - 1 = 0\\\\3x = 1\\\\x = 1/3\\\\\\3x - 1 = 0\\\\3x = 1\\\\x = 1/3[/tex]
Explicación paso a paso:
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
[tex]9x^2 - 6x + 1 = 0\\\\\frac{(9x - 3)(9x - 3)}{9}\\\\\frac{3(3x - 1)3(3x - 1)}{9}\\\\(3x - 1)(3x - 1)\\\\3x - 1 = 0\\\\3x = 1\\\\x = 1/3\\\\\\3x - 1 = 0\\\\3x = 1\\\\x = 1/3[/tex]
Explicación paso a paso: